Engineering antimicrobial and anti-photooxidative films via a cyclodextrin metal-organic frameworks encapsulation strategy for Mongolian cheese preservation - Liying Yang; Long Chen; Jiaming Deng; Douxin Xiao; Wenyan Zhao; Alideertu Dong (Food Research International, 2026)

Nickel from olivine dissolution induces diel photodamage and metabolic adjustment in Gracilariopsis lemaneiformis - Chang Liu; Dong Xu; Xuewei Wang; Yiqun Wu; Yuan Chang; Jiaming Zhang; Xinyu Qian; Ling Liu; Ping Li; Zhi-Hua Li (Journal of Hazardous Materials, 2026)

SMOTE-DNN algorithm for accurate recognition and classification of VAHs with minimal dataset requirements - Zijian Zhang; Jiaming Li; Wu Wang; Zhengmao Cao; Qingqing Ye; Chenyu Du; Ye He; Yanjuan Sun; Behzad Rezaei; Jianping Sheng; Fan Dong (Environmental Research, 2026)

Bioavailable heavy metals drive spatial reassembly and functional reprogramming of soil bacterial communities in electroplating-impacted farmland - Yaoben Lin; Jiaming Zhao; Dong Wang; Xinliang Wang (Applied Soil Ecology, 2026)

Gaδ+-H active sites-driven reverse water gas shift reaction with high CO selectivity - Zhenzhong Tao; Huaixiang Li; Dedong He; Zijun Huang; Jun Liang; Jiaming Dong; Xiaohua Cao; Yongming Luo (Chemical Engineering Journal, 2026)

Identification of electromechanical participation matrices via scaled-derivative DMDc for improved PPF active vibration control of thin-walled structures - Qinshan Ouyang; Longlei Dong; Jian Liu; Jiaming Zhou (Engineering Structures, 2026)

Defect-triggered S-scheme heterojunction coupled with single-molecular catalytic centers towards selective photocatalytic CO2 reduction to CO - Keyu Cui; Yujia Wang; Xingjing Zhang; Jiaming Li; Chunbo Liu; Liqiu Zhang; Hongjun Dong; Chunmei Li (Chemical Engineering Journal, 2026)

Synergistic effect in dual-site catalyst with silanol-stabilized Co2+-bonded Ni clusters for methane dry reforming - Zijun Huang; Dedong He; Han Xiao; Jun Liang; Jiaming Dong; Zhenzhong Tao; Xiaohua Cao; Dingkai Chen; Yongming Luo (Chemical Engineering Journal, 2026)

Fatty Acid-binding Protein 4 Exacerbates Blood–brain Barrier Disruption Through the JNK/c-Jun/MMP12 Pathway After Traumatic Brain Injury - Botao Ma; Dezhen Yang; Mengwu Tian; Shimei Dai; Zhuang Jing; Xuerui He; Xiaoqing Bao; Yinbo Long; Yu Gong; Yanling Dong; Jiaming Li; Gengshen Zhang; et al. (Molecular Neurobiology, 2026)

Artificial intelligence, environmental regulation and urban sustainable development: an empirical analysis of 287 cities in China - Kai Dong; Yang Ge; Tianxiang Sheng; Qianyun Weng; Jiaming Miao; Yanxin Cheng (Clean Technologies and Environmental Policy, 2026)

The effect of hydroxyl groups and humidity on the adsorption capacity of amine-functionalized macroporous resins for direct air capture - Jiaming Wang; Xiaohan Weng; Tao Han; Yongqiang Wang; Jinning Yang; Chao Zhou; Dong Xu; Liying Liu (Chemical Engineering Journal, 2025)

Activation of MnOOH/γ-Bi2MoO6 composites for RhB degradation by peroxymonosulfate - Xiaoya Liang; Dan Zhao; Yanmao Dong; Shuqi Fan; Xinhao Yue; Jiaming Qin (Journal of Water Process Engineering, 2025)

Adaptive isoline interval optimization for precise contour segmentation and instance-level detection of Martian impact craters - Dong Chen; Fan Hu; Jiaming Na; Zhenxin Zhang; Zhen Cao; Liqiang Zhang; Zhizhong Kang; Jiju Poovvancheri; Norbert Pfeifer (Icarus, 2025)

Spontaneous development and characterization of an endothelial-like cell line from mandarin fish Siniperca chuatsi - Jiaming Chen; Zhong Mi; Wenfeng Zhang; Panpan Luo; Shaoping Weng; Jianguo He; Chuanfu Dong (Fish & Shellfish Immunology, 2025)

The links between Na/K ratios in eolian sands and mean annual precipitation in the deserts of arid region, northern China - Jiaqi Wang; Shipei Dong; Zhuolun Li; Jiaming Qu; Yuhan Kuai; Dianjia Tan; Jie Luo (CATENA, 2025)

Selective expansion of TCF7-expressing tumor-reactive T cell subpopulations during ovarian tumor-infiltrating T cell production ex vivo - Dingfeng Liu; Ting Zhang; Qinli Sun; Dongli Cai; Yanan Lou; Genyu Wang; Bowen Xie; Yicheng Zhu; Chong Wang; Zhouping Lu; Chenfei Liu; Yuan Li; et al. (Science China Life Sciences, 2025)

Numerical Simulation of an Icebreaker Ramming the Ice Ridge - Wenbo Dong; Jiaming Chen; Yufei Zhang; Shisong Wei; Guangwei He; Fang Li (Journal of Marine Science and Engineering, 2025)
During polar navigation, icebreakers frequently encounter ice ridges, which can significantly reduce navigation efficiency and even pose threats to structural safety. Therefore, studying the ramming of ice ridges by the icebreaker is of great importance. In this study, the ice ridge is decoupled into the consolidated layer and the keel for modeling. The consolidated layer is simplified as layered ice, and an innovative hybrid empirical–numerical method is used to determine the icebreaking loads. For the keel, a failure model is developed using the Mohr–Coulomb criterion in combination with the effective stress principle, accounting for shear failure in porous media and incorporating both cohesion and internal friction angle. The ship is restricted to surge motion only. A comparative analysis with the model test results was conducted to assess the accuracy of the method, with the predicted ice resistance showing deviation of 9.85% in the consolidated ice area and 10.48% in the keel area. Ablation studies were conducted to investigate the effects of different ice ridge shapes, varying retreat distances, and different ship drafts on the performance of ramming the ice ridge. The proposed method can quickly and accurately calculate ice ridge loads and predict their motion responses, providing a suitable tool for on-site rapid navigability assessment and for the design of icebreakers.

Robust smartphone-assisted cellulosic smart label for real-time monitoring shrimp freshness under low temperature and high humidity conditions - Yilin Wang; Jiaming Wu; Dong Lv; Yehan Tao; Jinwen Hu; Chenglong Fu; Xiaodong Xia; Jijuan Cao; Haisong Wang; Jian Du (Chemical Engineering Journal, 2025)

Scale drop disease virus (SDDV) triggers ferroptosis both in mandarin fish (Siniperca chuatsi) and MFF-1 cells to facilitate virus infection via linking to transferrin receptor 1 (TfR1) - Jiaming Chen; Yuting Fu; Shuyi Chen; Shaoping Weng; Jianguo He; Chuanfu Dong (Fish & Shellfish Immunology, 2025)

Dynamic response of seabed in wind power of deep-shallow sea induced by internal solitary waves - Jiaming Xiang; Zhuangcai Tian; Youkou Dong; Enjin Zhao; Lei Song; Jianhua Yue; Guoqing Zhou; Xiaolei Liu; Xiujun Guo; Yonggang Jia (Marine Georesources & Geotechnology, 2025)

GACraterNet: A collaborative geometry-attribute domain network for enhanced detection of Martian impact craters - Fan Hu; Dong Chen; Jiaming Na; Zhen Cao; Zhenxin Zhang; Liqiang Zhang; Zhizhong Kang (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Effects of chlorpyrifos stress on the Eriocheir sinensis suffering from Metschnikowia bicuspidata infection - Jiaming Dong; Yuanyuan Tan; Chengcheng Feng; Qingbiao Hu; Yanhong Zhao; Jie Bao; Hongbo Jiang (Aquaculture, 2025)

Structural characterization of archaeal GDGT cyclization: Linking physiological adaptation to paleotemperature reconstruction - Jiaming Zhou; Liang Dong (Earth and Planetary Science Letters, 2025)

pLM33 provides tolerance of persistent Listeria monocytogenes ST5 to various stress conditions and also enhances its virulence - Xin Liu; Tianqi Shi; Jiaming Li; Huanyu Wu; Qing Zhao; Zhixin Fang; Yingying Liang; Quan Xiao; Min Chen; Qingli Dong; Hongzhi Zhang (Food Microbiology, 2025)

Chronic chlorpyrifos exposure induces oxidative stress, neurological damage, and hepatopancreas enrichment in Chinese mitten crab (Eriocheir sinensis) - Yuanyuan Tan; Jiaming Dong; Luyao Wang; Weining Li; Jie Bao; Hongbo Jiang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Preparation of a smart nano-herbicide MP@HLDP with strong permeability performance improves herbicidal activity while reducing the adverse impacts - Xile Deng; Zeng Wang; Jiaming Yin; Zhichao Dong; Jie Shen; Shuo Yan; Lianyang Bai (Chemical Engineering Journal, 2025)

Anti-PD-L1 blockade facilitates antitumor effects of radiofrequency ablation by improving tumor immune microenvironment in hepatocellular carcinoma - Jiahua Liang; Mingjian Ma; Wei Feng; Qiongcong Xu; Dong Chen; Jiaming Lai; Jiancong Chen (Apoptosis, 2025)

Fish Community Diversity and Spatiotemporal Dynamics in the Downstream of the Fujiang River Based on Environmental DNA - Jiaming Zhang; Yifang Chen; Xinxin Zhou; Jiaxin Huang; Xiaohan Dong; Shuli Zhu; Yanjun Shen (Fishes, 2025)
Hydrological changes caused by dam construction are among the primary drivers of global freshwater biodiversity decline. To assess the current status of fish community diversity and examine the impacts of cascade hydropower development on fish diversity, this study employed environmental DNA (eDNA) technology from 2023 to 2024 to conduct seasonal surveys at 18 sampling sites across six river segments separated by five dams in the downstream section of the Fujiang River. The study aimed to uncover the temporal and spatial dynamics of fish diversity and community structure, as well as to analyze the influence of environmental factors on these patterns. The results identified 84 fish species spanning 60 genera, 19 families, and 7 orders, including 2 nationally protected species, 11 endemic species of the upper Yangtze River, and 13 alien species. The cascade dams were found to have significantly reduced fish diversity compared to historical records, with a marked decline in native species and a rise in alien species, contributing to the miniaturization and homogenization of fish communities. Environmental factor analysis revealed that chemical oxygen demand (COD), dissolved oxygen (DO), total dissolved solids (TDS), electrical conductivity (EC), and reservoir formation time were significant drivers of fish community structure and diversity. This study provides essential baseline data on fish diversity under the influence of cascade hydropower development in the Fujiang River. It also offers valuable insights into the current status of fish resources and supports efforts in fish conservation and aquatic ecosystem management in the region.

Achieving remarkable charge transfer through the depolarization field in the 2D/2D S-scheme heterojunction consisted of C3N5 nanosheets and layered ferroelectric Bi3TiNbO9 for photocatalytic hydrogen production - Haotian Guo; Jinhui Jiang; Jiaming Liang; Chunyang Wen; Xinguo Xi; Pengyu Dong (Chemical Engineering Journal, 2025)

SbSeI for high-efficient photocatalytic degradation of multiple pollutants - Kang Li; Yue Gao; Zhongxin Dong; Huibo Zhang; Xudong Fan; Lei Xu; Jie Huang; Feng Teng; Haibo Fan; Jiaming Song; Chunmei Zhang; Xuexia He; et al. (Environmental Research, 2024)

Quasi-homogeneous photoelectrochemical organic transformations for tunable products and 100% conversion ratio - Cheng Lin; Yuan Lu; Jiaming Miao; Zhongyuan Ma; Youngmoon Choi; Yan Yang; Chaoran Dong; Jinyou Shen; Jong Hyeok Park; Kan Zhang (Science Bulletin, 2024)

A strategy for treatment of low-grade ore: Efficient separation and purification of iron - Shishun Dong; Ting Li; Jiaming Yu; Qifeng Wei; Xiulian Ren (Process Safety and Environmental Protection, 2024)

Structural insights linking H-bridging of archaeal GDGTs to high temperature - Jiaming Zhou; Liang Dong (Science of The Total Environment, 2024)

The role of HMGB2 in the immune response of Nile tilapia (Oreochromis niloticus) to streptococcal infection - Yuhang Dong; Zhiqiang Zhang; Yongxiong Huang; Xuyan Tan; Xing Li; Meiling Huang; Jiaming Feng; Yu Huang; Jichang Jian (Fish & Shellfish Immunology, 2024)

Recent research progress of MOFs-based heterostructures for photocatalytic hydrogen evolution - Jiaming Li; Jia Jia; Deping Wang; Hongjun Dong; Mingshan Zhu (Chemical Engineering Journal, 2024)

Enhanced reductive degradation of trichloroethylene by ball milled nitridation of bimetallic Ni-ZVI: Combination effect of electron transfer and catalytic hydrogenation - Yinghao Shi; Dong Wang; Jiaming Guo; Feilong Gao; Linan Liu; Jingchun Tang (Journal of Cleaner Production, 2024)

Erratum to: Low-intensity pulsed ultrasound ameliorates angiotensin II-induced cardiac fibrosis by alleviating inflammation via a caveolin-1-dependent pathway - Kun Zhao; Jing Zhang; Tianhua Xu; Chuanxi Yang; Liqing Weng; Tingting Wu; Xiaoguang Wu; Jiaming Miao; Xiasheng Guo; Juan Tu; Dong Zhang; Bin Zhou; et al. (Journal of Zhejiang University-SCIENCE B, 2024)

Binary-Network structured PI@SiO2 nanofibrous composite aerogels with temperature invariant superelasticity for thermal insulation - Qicheng Xue; Nanxi Dong; Peiqi Fan; Daolei Lin; Guofeng Tian; Jun Liu; Jiaming Wei; Shengli Qi; Dezhen Wu (Chemical Engineering Journal, 2024)

Effect of temperature on the occurrence of Metschnikowia bicuspidata disease in Eriocheir sinensis - Hongbo Jiang; Gangnan Cao; Jie Bao; Chengcheng Feng; Xiaodong Li; Yuanyuan Tan; Jiaming Dong; Qijun Chen (Aquaculture, 2024)

A novel forestry information-collecting mobile system - Shun Yao; Jiaming Zhang; Jiangming Kan; Ruifang Dong (Computers and Electronics in Agriculture, 2024)

Minor chromium passivation of S-ZVI enhanced the long-term dechlorination performance of trichlorethylene: Effects of corrosion and passivation on the reactivity and selectivity - Jiaming Guo; Dong Wang; Yinghao Shi; Honghong Lyu; Jingchun Tang (Water Research, 2024)

Molecular dynamics simulations reveal methylation in Me-GDGTs as a microbial low-temperature adaptation - Jiaming Zhou; Liang Dong (Chemical Geology, 2024)

Integrated scheduling problems of open shop and vehicle routing using an ensemble of group teaching optimization and simulated annealing - Jiaming Su; Yaping Fu; Kaizhou Gao; Hongyu Dong; Jianhui Mou (Swarm and Evolutionary Computation, 2023)

Zwitterionic loose polyamide nanofiltration membrane with good antifouling properties for efficient removal of humic acid and dyes - Chengbao Geng; Fangbo Zhao; Hongyan Niu; Jiaming Zhang; Yang Liu; Lijia Liu; Hongxing Dong; Zhiguo Li; Hongxu Chen (Journal of Environmental Chemical Engineering, 2023)

Experimental study on the characteristics of radiation floor cooling system based on an earth–air heat exchanger - Jiaming Yang; Wei Song; Houan Zhang; Jing Wang; Jiankai Dong (Energy and Buildings, 2023)

Comparing extraction methods for analyzing n-alkyl lipids in shelf sediments from the China Sea - Jiaming Zhou; Xiaoxiao Zhao; Xin Chen; Liang Dong (Organic Geochemistry, 2023)

Effects of Dietary Lentinus edodes Fermentation Supplementation on Digestive Enzyme Activity, Antioxidant Capacity and Morphology of the Liver and Intestine in Largemouth Bass (Micropterus salmoides) Fed High Plant Protein Diets - Jiaming Xu; Zhoulin Yu; Guangye Liu; Sijie Li; Guoyong Zhou; Hanhua Wang; Yewei Dong; Cuihong You; Weidong Bai; Meng Zhou; Yanhua Huang; Xiaohong Tan (Fishes, 2023)
This study evaluated the effect of Lentinus edodes fermentation (LEF) on digestive enzyme activity, antioxidant capacity and morphology of the liver and intestine in largemouth bass (Micropterus salmoides) fed high plant protein diets (HPPD). LEF was supplemented in HPPD with 0 g kg−1 (LEF0), 10 g kg−1 (LEF1), 20 g kg−1 (LEF2), 30 g kg−1 (LEF3), 40 g kg−1 (LEF4), 50 g kg−1 (LEF5), respectively, and then the six diets were fed to largemouth bass with a body weight of 28.8 ± 0.05 g for eight weeks. Juvenile fish were randomized into 6 groups and each group had 4 replicates with 40 fish. Dietary LEF supplementation alleviated the liver inflammatory reaction of largemouth bass caused by HPPD and improved liver morphology. Goblet cells multiplied and the gut muscle layer thickened after LEF supplementation. The LEF significantly increased amylase activity in the liver and intestine of largemouth bass in individual experimental groups. The LEF could increase the activity of catalase in the liver and intestine of largemouth bass (p

Magnetic nanometer combined with microwave: Novel rapid thawing promotes phenolics release in frozen-storage lychee - Canhua Xu; Jiaming Lu; Qingzhu Zeng; Junjia Zhang; Lihong Dong; Fei Huang; Yingbin Shen; Dongxiao Su (Food Chemistry, 2023)

A mandarinfish Siniperca chuatsi infection and vaccination model for SDDV and efficacy evaluation of the formalin-killed cell vaccine in yellowfin seabream Acanthopagrus latus - Yuting Fu; Yong Li; Jiaming Chen; Fangzhao Yu; Xiangrong Liu; Weixuan Fu; Hongrun Pan; Wangdong Li; Shaoping Weng; Jianguo He; Chuanfu Dong (Aquaculture, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Evaluation of intervention effects of dietary coenzyme Q10 supplementation on oxidized fish oil-induced stress response in largemouth bass Micropterus salmoides - Yuexing Zhang; Linwei Cai; Zhiyong Dong; Bowen Wu; Yangyang Gong; Baoping Zhang; Bo Wang; Jiaming Kang; Tianhong Ke; Zhijin Xu; Trond Storebakken; Bo Shi (Fish & Shellfish Immunology, 2023)

Ancient and modern mitogenomes of red deer reveal its evolutionary history in northern China - Bo Xiao; Tianjiao Wang; Adrian M. Lister; Junxia Yuan; Jiaming Hu; Shiwen Song; Haifeng Lin; Siren Wang; Chunxue Wang; Dong Wei; Xulong Lai; Xiumei Xing; et al. (Quaternary Science Reviews, 2023)

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

Low-intensity pulsed ultrasound ameliorates angiotensin II-induced cardiac fibrosis by alleviating inflammation via a caveolin-1-dependent pathway - Kun Zhao; Jing Zhang; Tianhua Xu; Chuanxi Yang; Liqing Weng; Tingting Wu; Xiaoguang Wu; Jiaming Miao; Xiasheng Guo; Juan Tu; Dong Zhang; Bin Zhou; et al. (Journal of Zhejiang University-SCIENCE B, 2021)

CDKN1B Mediates Apoptosis of Neuronal Cells and Inflammation Induced by Oxyhemoglobin via miR-502-5p After Subarachnoid Hemorrhage - Dong Chen; Xianwei Wang; Jiaming Huang; Sifu Cui; Liqiang Zhang (Journal of Molecular Neuroscience, 2020)

Study on the synergy between intra-urban resident’s migration and job change in Beijing - Jianhui Yu; Guanpeng Dong; Wenzhong Zhang; Jiaming Li (Journal of Geographical Sciences, 2015)

Contribution of the IBD5 locus to inflammatory bowel disease: a meta-analysis - Jian Wang; Xi Wang; Hong Yang; Dong Wu; Li Wang; Jiaming Qian (Human Genetics, 2011)